Microneedle Array Patches Integrated with Nanoparticles for Therapy and Diagnosis. Issue 4 (18th January 2021) - Hu, Xiuli; Zhang, Huijuan; Wang, Zejun; Shiu, Chin Ying Angela; Gu, Zhen
Abstract : Microneedle (MN)‐based techniques are widely explored these years for biomedical applications due to their convenience, high efficiency, and excellent patient compliance. The combination of MN array patches with nanoparticles (NPs) expands the applications of MNs with dynamic characteristics and facilitates on‐demand drug release while reducing systemic toxicity and enhancing therapeutic efficacy. This review summarizes the recent advances of MNs integrated with NPs as a transdermal approach for various applications. Representative therapeutic or diagnostic studies associated with diabetes, cancer, vaccine, obesity, hair growth, and acne vulgaris are highlighted in detail. Future perspectives for such theranostic devices in biomedical fields are also discussed. Abstract : Various nanoparticles, such as micelles, nanovesicles, nanogel, complex, and nanonetworks, are integrated with microneedles for biomedical applications with enhanced efficacy. Representative therapeutic or diagnostic studies, including diabetes, cancer, vaccine, obesity, hair growth, and acne vulgaris, are highlighted.